The Influence of Independence, Leadership Style, Organizational Commitment, Audit Experience, Due Professional Care and Job Satisfaction on Auditor Performancei Public Accounting Office for Medan Region - Sri Margaretha Purba; Lola Theresia Sidabariba; Harry Manalu; Eisen Howar Wilem Simatupang (Budapest International Research and Critics University, 2023)
This research was conducted to analyze the effect of Independence, Leadership Style, Organizational Commitment, Audit Experience, and Due Professional Care on Auditor Performance with Job Satisfaction as a Moderating Variable in the Medan Regional Public Accounting Firm. The population used in this study were all auditors working at KAP in Medan City. Sampling was carried out using purposive sampling method, and the number of samples was 60 respondents. Data collection method is done with primary data and secondary data by using a questionnaire. The data analysis technique used in this research is multiple linear regression analysis technique. The results of this study indicate that independence, leadership style, organizational commitment, audit experience, and due professional care simultaneously have a negative effect on auditor performance and also on job satisfaction at KAP in Medan. Partially independence, leadership style, organizational commitment, performance satisfaction, and due professional care have a negative effect on performance as well as auditor job satisfaction at KAP in Medan.